The Empirical Economist's Toolkit: From Models to Methods - Matthew T. Panhans; John D. Singleton (Duke University, Center for the History of Political Economy (CHOPE), 2015)
While historians of economics have noted the transition toward empirical work in economics since the 1970s, less understood is the shift toward -experimental" methods in applied microeconomics. Angrist and Pischke (2010) trumpet the wide application of these methods as a revolution" in econometrics that has nally provided persuasive answers to a diverse set of questions. Particularly in uential in the applied areas of labor, education, public, and health economics, the methods shape the knowledge produced by economists and the expertise they possess. First documenting their growth bibliometrically, this paper aims to illuminate the origins, content, and contexts of quasi-experimental research designs, which seek natural experiments to justify causal inference. To highlight lines of continuity and discontinuity in the transition, the quasi-experimental program is situated in the historical context of the Cowles econometric framework and a case study from the economics of education is used to contrast the practical implementation of the approaches. Finally, signi cant historical contexts of the paradigm shift are explored, including the marketability of quasi-experimental methods and the 1980s crisis in econometrics.
Keywords: B21; B23; B4; C1; 330; econometrics; quasi-experimental methods; natural experiments; applied economics